Severe Acute Respiratory Syndrome Coronavirus 2 Surveillance in Decedents in a Large, Urban Medical Examiner's Office. (2nd September 2020) - Brouwer, Andrew F; Myers, Jeffrey L; Martin, Emily T; Konopka, Kristine E; Lauring, Adam S; Eisenberg, Marisa C; Lephart, Paul R; Nguyen, Teresa; Jaworski, Andrea; Schmidt, Carl J
Abstract: Background: Given the challenges in implementing widespread testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there is increasing interest in alternative surveillance strategies. Methods: We tested nasopharyngeal swabs from 1094 decedents in the Wayne County Medical Examiner's Office for SARS-CoV-2. All decedents were assessed using a coronavirus disease 2019 (COVID-19) checklist, and decedents flagged using the checklist (298) were preferentially tested. A random sample of decedents not flagged using the checklist were also tested (796). We statistically analyzed the characteristics of decedents (age, sex, race, and manner of death), differentiating between those flagged using the checklist and not and between those SARS-CoV-2–positive and not. Results: A larger percentage of decedents overall were male (70% vs 48%) and black (55% vs 36%) compared with the catchment population. Seven-day average percent positivity among flagged decedents closely matched the trajectory of percent positivity in the catchment population, particularly during the peak of the outbreak (March and April 2020). After a lull in May to mid-June, new positive tests in late June coincided with increased case detection in the catchment. We found large racial disparities in test results; SARS-CoV-2–positive decedents were substantially more likely to be black than SARS-CoV-2–negative decedents (82% vs 51%). SARS-CoV-2–positive decedents were also more likely to be older and to have died of natural causes, including of COVID-19 disease. Conclusions: Disease surveillance through medical examiners and coroners could supplement other forms of surveillance and serve as a possible early outbreak warning sign. Abstract : We piloted severe acute respiratory syndrome coronavirus 2 surveillance in decedents in a large, urban medical examiner's office. Longitudinal test positivity among decedents flagged using a coronavirus disease 2019 checklist closely matched testing in the catchment population.